2008
DOI: 10.1080/09297040701595505
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Lexical and Sublexical Reading Skills in Children with Neurofibromatosis Type 1

Abstract: Neurofibromatosis type 1 (NF1) is an inherited neurocutaneous disorder associated with a high frequency of cognitive and learning difficulties. Based on discrepancies between IQ and academic achievement, approximately 17% of children with NF1 have been classified as having reading impairments. In this study, the lexical and sublexical reading skills of children with NF1 (n = 30) were examined using the Castles' Word/Non-Word Test (modified version), together with measures of neuropsychological functioning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 37 publications
4
29
2
Order By: Relevance
“…Of note, we found strong correlations between phonological awareness and letter‐sound knowledge in our NF1 cohort, which suggests these two skills typically develop in parallel in NF1; or, at least, that when there is a delayed development in one of these skills, there is usually poor development in the other. Taken together, these findings suggest that weak letter‐sound knowledge ultimately appears to be the most important predictor of early spelling ability in NF1, and that deficits in letter‐sound knowledge in combination with phonological impairments are likely to significantly contribute to the literacy difficulties that are common in school‐aged children with the condition …”
Section: Discussionmentioning
confidence: 83%
“…Of note, we found strong correlations between phonological awareness and letter‐sound knowledge in our NF1 cohort, which suggests these two skills typically develop in parallel in NF1; or, at least, that when there is a delayed development in one of these skills, there is usually poor development in the other. Taken together, these findings suggest that weak letter‐sound knowledge ultimately appears to be the most important predictor of early spelling ability in NF1, and that deficits in letter‐sound knowledge in combination with phonological impairments are likely to significantly contribute to the literacy difficulties that are common in school‐aged children with the condition …”
Section: Discussionmentioning
confidence: 83%
“…Although it is true that most children with NF-1 show visuospatial impairment, a variety of other (and more academically relevant) deficits have been noted, including those in the reading, language, and memory domains (Hyman, Shores, & North, 2006; Krab et al 2008; Levine, Materek, Abel, O’Donnell, & Cutting, 2006; Watt, Shores, & North, 2008). Because of the tremendous importance of reading for life achievement, particularly regarding their children’s school and employment future, weaknesses in reading are often of utmost concern for parents and teachers (Krab et al; Stine and Adams, 1989), and almost all studies that have examined reading abilities in NF-1 have reported deficits in this area (e.g., Brewer, Moore, & Hiscock, 1997; Cutting, Koth, & Denckla, 2000; Dilts et al, 1996; Hofman, Marris, Bryan, & Denckla, 1994; Mazzocco et al, 1995; Mautner, Kluwe, Thakker, & Leark, 2002; North et al, 1994; North, 2000; Watts et al, 2008).…”
Section: Learning Disabilities In Nf-1mentioning
confidence: 99%
“…Concerning the DL findings, to the best of our knowledge, only one study examined lexical and phonological reading skills in children with NF1 (Watt et al, 2008). The authors reported 67% of the sample exhibited deficits in one or more reading skills.…”
Section: Discussionmentioning
confidence: 99%
“…SLD have been reported in 30–70% of children with NF1 (Hyman et al, 2005; Acosta, 2007). Nevertheless, the diagnosis of SLD has mainly focused on IQ-achievement discrepancy (Hyman et al, 2005; Watt et al, 2008). The discrepancy model has been criticized for numerous authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation